On the modeling of a prefracture zone near the crack front - Kaminsky, A.A. (Reports of the National Academy of Sciences of Ukraine, 2015)
A critical analysis of the current state of the modeling problem for the fracture of a material in a vicinity of the crack tip is performed. Theoretical approaches to an adequate description of the experimental behavior of materials during their fracture as a result of the crack propagation are considered. The assessment of the perspectives of various approaches to the future development of the current models is given.